Oral traditions in Malaysia; A discussion of shamanism - Daud, Haron (Wacana, Journal of the Humanities of Indonesia, 2010)
The article discusses Malay oral traditions and emphasizes the shamanistic aspects of these traditions. Shamans often recite mantras in the execution of their role in society. The role of the shaman, their self proclaimed knowledge, shamans and their economic activities, black magic and healthcare in Malay society are discussed, as well as the shaman's role in Dayak ritual. Each aspect is discussed in combination with the mantra the shaman utters.